Analysis of the Effect of Financial Performance on Stock Returns in Manufacturing Companies (Basic Industry & Chemical Sector, Cement Sub-Sector Listed on the IDX for the 2018 – 2020 Period) - Ndruru, Ariston (Interconnection: An Economic Perspective Horizon, 2023)
This study aims to determine the analysis of the effect of financial performance on the company's stock returns. The financial ratios used in this research are Current Ratio, Det to Equity Ratio and Total Asset Turn Over. This study uses secondary data, namely the financial statements of manufacturing companies in the basic industrial sector and the cement sub-sector chemical listed on the Indonesia Stock Exchange in the period 2018 – 2020. This financial report is accessed through www.idx.id. The population in this study are all manufacturing companies in the basic and chemical industry sectors listed on the IDX in the 2018-2020 period. The data collection method is purposive sampling so that the number of samples obtained is 6 companies with 3 years of observational financial statements. Data analysis techniques used are descriptive statistics and multiple linear regression analysis. The first analysis process uses descriptive statistics, classical assumption test, multiple regression analysis and then hypothesis testing. The results of this study partially show that CR, DER and TATO have no effect on stock returns in manufacturing companies in the basic and chemical industrial sectors listed on the IDX for the period 2018-2020.